CHRONIC DIARRHEA WITH CHRONIC GASTRITIS ON ELDERLY WOMEN - Elis Sri Alawiyah; Muhartono Muhartono (Fakultas Kedokteran Universitas Lampung, 2014)
Diarrheal disease is still a public health problem for Indonesia, because of its morbidity and mortality are still high. Morbidity survey conducted by Subdit Diarrhea, Department of Health from 2000 untill 2010 looks inclination incidence. In addition, there are also a number of chronic gastritis gastritis already so high that ranks 10th in the category of most diseases. Ny. N, 60 years old female came to the health center with a history of diarrhea since 3 days ago. Diarrhea more than 6 times a day, intermittent over the past 1 month, the color was yellow, and slimy. This complaint accompanied by nausea, decreased appetite, sometimesaccompanied by fever. Physical examination revealed blood pressure, pulse and breathing are normal but body temperature was 37.6 oC, sunken eyelids, dry lips, abdomen was convex, epigastric tenderness, increased bowel sounds. Diagnosis of these patients are chronic diarrhea and chronic gastritis. Therapy was Cotrimoxazole 2x1 tabs, Oralit (on each diarrhea), Zinc 1x1 tab, Paracetamol 3x1 tab, Antacid 3x1 tab. Chronic diarrhea in these patients caused by infection and non-infectious. While chronicgastritis caused by the bacterium Helicobacter pylory or psychological stress. [J Agromed Unila 2014; 1(2):126-131]Keywords: chronic diarrhea, chronic gastritis